2021
DOI: 10.1039/d0sc05813k
|View full text |Cite
|
Sign up to set email alerts
|

Rh(i)- and Rh(ii)-catalyzed C–H alkylation of benzylamines with alkenes and its application in flow chemistry

Abstract: Rh(i)- and Rh(ii)-catalyzed C–H alkylation of benzylamines with alkenes using a picolinamide derivative as a directing group is reported under both batch and flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…The same picolinamide directing group was further utilized for the Rh(I) and Rh(II) catalyzed C-H bond alkylation of benzylamine derivatives 20a (Scheme 20). 74 The reaction was compatible with various alkenes, including a,b-unsaturated alkenes and styrene derivatives. Several substituted benzylamines and thiophene derived amines were well tolerated in this reaction.…”
Section: Alkylation Of Aromatic C(sp 2 )-H Bondsmentioning
confidence: 93%
“…The same picolinamide directing group was further utilized for the Rh(I) and Rh(II) catalyzed C-H bond alkylation of benzylamine derivatives 20a (Scheme 20). 74 The reaction was compatible with various alkenes, including a,b-unsaturated alkenes and styrene derivatives. Several substituted benzylamines and thiophene derived amines were well tolerated in this reaction.…”
Section: Alkylation Of Aromatic C(sp 2 )-H Bondsmentioning
confidence: 93%
“…Not long ago, the same group found that Rh 2 (OAc) 4 could also be employed in the C–H alkylation of benzylamines with alkenes (Scheme 79). 132 Both picolinamide as well as other heterocycles such as a thiophene-derived amine were amenable for use as the directing group. The conditions of Rh( i ) as the catalyst also worked well, but were inferior in the substrate scope investigation.…”
Section: Dirhodium As a Redox Catalystmentioning
confidence: 99%
“…On the other hand, C–H alkylation with alkenes offers a much more environmentally friendly reaction because all the molecules of the substrates and alkenes are fully utilized in forming the desired products. Given our ongoing interest in C–H alkylation reactions, we investigated the ortho -alkylation of benzylamines with unactivated alkenes. In our previous work, we reported the Rh-catalyzed linear-selective, picolinamide chelation assisted C–H alkylation of benzylamine derivatives with activated alkenes, such as acrylates, styrenes, and maleimides .…”
mentioning
confidence: 99%